dCtBP mediates transcriptional repression by Knirps, Krüppel and Snail in the Drosophila embryo. - Nibu, Y (1998)
The pre-cellular Drosophila embryo contains 10 well characterized sequence-specific transcriptional repressors, which represent a broad spectrum of DNA-binding proteins. Previous studies have shown that two of the repressors, Hairy and Dorsal, recruit a common co-repressor protein, Groucho. Here we present evidence that three different repressors, Knirps, Krüppel and Snail, recruit a different co-repressor, dCtBP. Mutant embryos containing diminished levels of maternal dCtBP products exhibit both segmentation and dorsoventral patterning defects, which can be attributed to loss of Krüppel, Knirps and Snail activity. In contrast, the Dorsal and Hairy repressors retain at least some activity in dCtBP mutant embryos. dCtBP interacts with Krüppel, Knirps and Snail through a related sequence motif, PXDLSXK/H. This motif is essential for the repression activity of these proteins in transgenic embryos. We propose that dCtBP represents a major form of transcriptional repression in development, and that the Groucho and dCtBP co-repressors mediate separate pathways of repression.